An automated method for size and velocity distribution measurement in a particle-laden flow. (August 2019) - Niazi, Erfan; McDonald, James G.; Fenech, Marianne
Highlights: Detection of particles and classification according to their size. Construction of a velocity distribution function characterizing the motion of particles within each distinct size group. Determination of particle shape and orientation. Application to the complex flow of red blood cells with agglomeration and breakage. Through verification of the software for this application. Abstract: Over the past several decades, image processing and automated tracking of particles has emerged as a useful tool for the study of biological particles behaviour. This article describes an open-source computational implementation of a method for determining particle velocity and size distributions of large groups of particles by analyzing video sequences acquired using a video-microscopic systems. Although, in this study, red blood cells are used as a subject, this implementation can be used for any particle-laden flow where particles present a range of sizes and details of the velocity distribution of each size is of interest. From each single image, the current program detects particles and classifies them according to their size. It uses sequential images to track particles and compute the instantaneous velocity distribution of the particles. The tool can also assign an ellipse to each particle and report the major axis, the minor axis and the orientation of particles in each image. Use of the program improves repeatability of image processing and is suitable for studies related to particle dynamics, colloids, and microfluidic flow measurement. The size distribution and the velocity distribution of particles is often useful in the study of effect of parameters like shear stress on particle collision rate, agglomeration and breakage rate.